2011
DOI: 10.1073/pnas.1107913108
|View full text |Cite
|
Sign up to set email alerts
|

B cell-derived IL-10 suppresses inflammatory disease in Lyn-deficient mice

Abstract: Lyn kinase deficient mice represent a well established genetic model of autoimmune/autoinflammatory disease that resembles systemic lupus erythematosus. We report that IL-10 plays a crucial immunosuppressive role in this model, modulating the inflammatory component of the disease caused by myeloid and T-cell activation. Double-mutant lyn −/− IL-10 −/− mice manifested severe splenomegaly and lymphadenopathy, dramatically increased proinflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 57 publications
7
59
0
Order By: Relevance
“…2B). As previously observed, the lyn −/− mice had elevated levels of Th1 (IFN-γ) and Th17 (IL-17), but not Th2 (IL-4 and IL-13) cytokines, as well as increased levels of IL-6, IL12-p40, G-CSF, GM-CSF and a number of chemokines (KC, MIG, MIP-1α/β and IP10) (16). Similar changes were also observed in the lyn f/f Cd11c-cre + animals (Fig.…”
Section: Dc-specific Lyn Deletion Leads To the Development Of Nephritsupporting
confidence: 50%
“…2B). As previously observed, the lyn −/− mice had elevated levels of Th1 (IFN-γ) and Th17 (IL-17), but not Th2 (IL-4 and IL-13) cytokines, as well as increased levels of IL-6, IL12-p40, G-CSF, GM-CSF and a number of chemokines (KC, MIG, MIP-1α/β and IP10) (16). Similar changes were also observed in the lyn f/f Cd11c-cre + animals (Fig.…”
Section: Dc-specific Lyn Deletion Leads To the Development Of Nephritsupporting
confidence: 50%
“…This suggests a link between autoimmunity and inflammation in susceptible mice. The proinflammatory cytokine IL-6 is elevated in the serum from some aged Lyn À/À mice [16,47], and it has been shown that the increase in myeloid progenitors and myeloid cell expansion is dependent on IL-6 [16]. Interestingly, while IL-6 levels were reduced in p110d þ/KD serum compared to controls, levels were similarly elevated in the serum of some aged Lyn À/À and Lyn À/À p110d þ/KD mice (Fig.…”
Section: Altered Proliferation Of Lyn à/à P110d þ/Kd B Cellsmentioning
confidence: 52%
“…Since Lyn À/À B cells are the major producers of IL-6 [16], this suggests that this phenotype is unaltered by haploinsufficiency of p110d. The anti-inflammatory cytokine IL-10 has been shown to be increased in the serum of aged Lyn À/À mice [47] where it is believed to play a role in suppressing the inflammatory environment and autoimmune disease development. We have confirmed that IL-10 is elevated in the serum of aged Lyn À/À mice, and have found that it is similarly elevated in the serum of aged Lyn À/À p110d þ/KD mice (Fig.…”
Section: Altered Proliferation Of Lyn à/à P110d þ/Kd B Cellsmentioning
confidence: 99%
“…56,57 The phenotype can be partially explained by increased Mpl-mediated Erk1, Erk2, and Akt activation in Lyn-deficient megakaryocytes. SHIP-1 phosphorylation is concomitantly decreased, suggesting that Lyn negatively regulates the Ras/MAPK and PI3K/Akt pathways in a SHIP-1-dependent manner.…”
Section: Dual Roles Of Lyn In Itam-containing and Integrin Receptor Smentioning
confidence: 99%